Model of University Entrepreneurial Education Development Strategy for Preparing the Golden Generation Toward 2045: Islamic Entrepreneurship Perspective - Hendra Halim; Fadhil, Rahmat; Rahimi, Sayyid Afdhal El (Asian Journal of Management Analytics, 2024)
This study aims to develop entrepreneurial strategies based on sharia principles at Universitas Syiah Kuala to prepare students for Indonesia’s Golden Era 2045. Key concepts explored include sharia-based entrepreneurship education, curriculum reform, and business incubation. Using Soft Systems Methodology (SSM), the research identifies and implements changes through curriculum redesign, workshops, strategic partnerships, and the establishment of a sharia business incubator. Data collection involved surveys and interviews with students, faculty, and local business stakeholders over six months. The results indicate increased student engagement and business creation aligned with sharia values. These findings highlight the importance of integrating Islamic principles into entrepreneurship education, offering valuable insights for other universities seeking to develop similar programs.